Contemporary Advertising. - Arens, William F (Boston : McGraw Hill, 2004)
This text showcases contemporary examples and practical applications of advertising. It presents advertising from the creative stand-point and draws from industry experience to invigorate the examples provided in the book.
Keywords: Advertising